A graphene-interlayered magnetic composite as a multifunctional SERS substrate1. Issue 76 (19th August 2015) - Xu, Jiawen; Wang, Chongwen; Rong, Zhen; Cheng, Xiang'ai; Xiao, Rui
<x xml:space="preserve">Abstract</x> Fe3O4@Ag-rGO-Au composites for efficient SERS detection of different analytes.